Mangled upper extremity: Our strategy of reconstruction and clinical results. Issue 12 (December 2021) - Georgescu, Alexandru Valentin; Battiston, Bruno
Highlights: The anatomical complexity of the upper limb and the need to obtain at least a lasting function makes the approach of these cases very challenging. The orthoplastic and microsurgical approach seems to be the better way in solving the mangled upper extremity. Main surgical steps: assessment of the patient and lesion; decision making; debridement; timing of reconstruction; reconstruction. The as early as possible reconstruction seems to offer the possibility to obtain the best functional results. The reconstruction of tissue defects should be done by using free flaps but, whenever possible, also local/regional flaps. Abstract: The management of mangled upper extremity is very challenging because the anatomical complexity of the region, the large number of possible involved anatomical elements, and the necessity of obtaining a good functionality. The impressive development of microsurgical techniques in the last decades contributed a lot to the salvage of several extreme injuries with mangled extremities considered untreatable in the past. Such injuries can nowadays be successfully managed by means of replantation/revascularization or complex reconstruction by using simple or complex microsurgical flaps. The more important steps in managing a mangled upper extremity are the decision making, the moment of reconstruction, the debridement, and the reconstruction by using customized methods. The decision regarding extremity salvage or amputation has to be individualized taking into account general and local factors. These factors influence the absolute or relative indication, but the final decision is up to the experience of every single surgical team. The timing of reconstruction is still a large debated subject, but it seems that the reconstruction as soon as possible is in the advantage of obtaining a much better functional recovery. The debridement should be very carefully performed in the attempt to preserve all the essential anatomical elements able to allow the obtaining of enough functionality. Most of these lesions are accompanied by simple or complex tissue defects. The coverage of these defects needs customized simple or composite flaps used both as free and local/regional microsurgical flaps. Based on the experience regarding the strategy and management of the mangled upper extremity in two European hand trauma centers, we conclude that the keystone in savaging this kind of lesions is represented by a very carefully assessment of the patient and lesion, an enough aggressive debridement, and an as soon as possible reconstruction.